The Nepal-Tibet War (1788-1792): A Historical Analysis - Pokharel, Arjun Prasad (Academia Research Journal, 2025)
The Nepal-Tibet War (1788–1792), also known as the Sino-Nepalese War, was a defining conflict in the history of the Himalayan region, involving the Gorkha Kingdom of Nepal, the Tibetan government under the suzerainty of the Qing Dynasty of China, and indirectly the interests of the British East India Company. This research article provides a comprehensive, multi-perspective examination of the war’s causes, progression, and consequences. The study employs a qualitative historical methodology that integrates primary Nepali court chronicles, Tibetan monastic records, Qing imperial edicts, and the observations of contemporary European traders and diplomats. The analysis situates the conflict within the broader geopolitical transformations of the late 18th century, including the expansionist policies of Nepal following its unification, the economic importance of trans-Himalayan trade routes, and Qing China's frontier defense strategy. The war began with Nepal’s incursion into Tibet in 1788 over coinage and trade disputes, escalated with the Qing military intervention in 1791, and concluded with the Treaty of Betrawati in 1792, which established a tributary relationship between Nepal and China. The findings demonstrate that the war was not only a product of immediate disputes but also a manifestation of structural economic rivalries, political ambitions, and cultural interactions. Its long-term impact included shifts in regional trade patterns, changes in military strategy, and enduring diplomatic precedents in Sino-Nepalese relations.